Foundations of the Nazi Police State : The Formation of Sipo and SD - Browder, George C., 1939- (Book collections on Project MUSE., 2004)
The abbreviation ""Nazi, "" the acronym ""Gestapo, "" and the initials ""SS"" have become resonant elements of our vocabulary. Less known is ""SD, "" and hardly anyone recognizes the combination ""Sipo and SD."" Although Sipo and SD formed the heart of the National Socialist police state, the phrase carries none of the ominous impact that it should. Although no single organization carries full responsibility for the evils of the Third Reich, the SS-police system was the executor of terrorism and ""population policy"" in the same way the military carried out the Reich's imperialistic aggression.